Ornithogalum beyazoglui (Hyacinthaceae), a new species from west Anatolia, Turkey - Bagci, Yavuz; Savran, Ahmet; Düsen, Olcay Dinç; Tutar, Lütfi (Bangladesh Journal of Plant Taxonomy, 2011)
Ornithogalum beyazoglui Y.Bagci, Savran & O. D. Düsen sp. nov. (Hyacinthaceae), a new species is described and illustrated from Ýzmir, Ödemis, Bozdag (Ýzmir, Ödemis province). Diagnostic morphological characters are discussed, including SEM examination of seed coat surface. Data are also presented on ecology, biogeography and conservation status of the new species.